2020
DOI: 10.3390/ani10040713
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Dairy Cattle Behavior in Different Barns in Northern Italy

Abstract: Due to its increasing pressure on dairy cows, studies that investigate how to cope with heat stress are needed. The heat stress affects multiple aspects of cows’ lives, among which their behavior and welfare. In this study, a survey was carried out in eight farms located in Northern Italy to monitor and evaluate the environmental aspects of the barns and the behavioral responses of dairy cows. For one year, three periods were monitored: thermoneutral (T_S), hot (H_S) and cold (C_S) seasons. Temperature and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…This is a significant aspect of the Precision Livestock Farming (PLF) approach, which is involving the livestock farming sector in a fast process and is providing farms with great opportunities of improvement of the production performance and the conditions of animal welfare, independently of the farm size [ 3 , 4 ]. In the dairy cattle sector, the availability of data recorded in real time concerning the environmental conditions of the barn and the production performances of the individual cows represent a quantitative knowledge basis with a huge potential of development of further informatic and electronic tools, able to achieve optimal conditions of animal welfare and more sustainable productions, in addition to improvements in milk quality and production efficiency [ 5 ]. In particular, the ever more widespread Automatic Milking Systems (AMSs) provide farmers with detailed data concerning health conditions and parameters connected to the milk produced, which are of great interest to optimize the production [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant aspect of the Precision Livestock Farming (PLF) approach, which is involving the livestock farming sector in a fast process and is providing farms with great opportunities of improvement of the production performance and the conditions of animal welfare, independently of the farm size [ 3 , 4 ]. In the dairy cattle sector, the availability of data recorded in real time concerning the environmental conditions of the barn and the production performances of the individual cows represent a quantitative knowledge basis with a huge potential of development of further informatic and electronic tools, able to achieve optimal conditions of animal welfare and more sustainable productions, in addition to improvements in milk quality and production efficiency [ 5 ]. In particular, the ever more widespread Automatic Milking Systems (AMSs) provide farmers with detailed data concerning health conditions and parameters connected to the milk produced, which are of great interest to optimize the production [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the area is poorly ventilated favoring the stagnation of pollutants and consequently contribute to the accumulation of PM ( Carugno et al, 2016 ). Lombardy is located in the middle of the Po valley and it is Italy's leading industrial and agricultural area ( Lovarelli et al, 2020 ), whose emissions (methane, ammonia, dinitrogen monoxide, etc.) worsen the air quality issue ( Rebolledo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The average milk production was recorded equal to 27.9 ± 6.5 kg/day, and cows lie down 10.6 ± 2.6 h/day, which is a quite low value compared to literature suggestions but still included within the range of adequate daily lying time. For example, Tullo et al (13) found that cows commonly lie down for about 9-14 h/day when reared indoors, while Lovarelli et al (14) showed that seasonality affects the lying time, in particular that the monitored cows lie down for a longer period in the cold season (on average 12.06 h/day) than in summer (on average 10.04 h/day). This supports also the findings in which a lower lying time is related to high THI conditions and in which high THI is associated with lower feed intake, lower milk production, and variations in behavior (9,11,17,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, for example, those reducing the negative effects caused by heat stress can play an important role. Natural and/or forced ventilation and shaded areas could improve the dairy cattle response to heat stress conditions that generally occur in summer (14,27,28). Specific feeding solutions with different frequency in feeding could also contribute in varying cow behavior (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation